2007
DOI: 10.1080/00173130601178250
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of pollen in the atmosphere of Darwin, tropical Australia: Preliminary results

Abstract: Pollen loads in the atmosphere of Darwin, a city located in the wet-dry tropics of Australia, have been monitored for the period March 2004 to November 2005 as part of a large research program looking at atmospheric particles and human health. Seven pollen types dominate the pollen spectrum, the herbaceous families of Poaceae (grasses) and Cyperaceae (sedges), as well as several native tree and shrub taxa, Acacia, Callitris, Casuarina, Arecaceae and Myrtaceae. The pollen loads were found to have a strong seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…Multiple peaks within a season may represent different species flowering at various temporal intervals and/or multiple flowering events for the same species in a year. For example, the flowering season of Gamba grass is noted to occur after that of native grasses in NT (Stevenson et al 2007). These variables have not been able to be evaluated on a broader scale as the pollen-monitoring methods used do not differentiate grass pollen to species level nor between C 3 and C 4 types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple peaks within a season may represent different species flowering at various temporal intervals and/or multiple flowering events for the same species in a year. For example, the flowering season of Gamba grass is noted to occur after that of native grasses in NT (Stevenson et al 2007). These variables have not been able to be evaluated on a broader scale as the pollen-monitoring methods used do not differentiate grass pollen to species level nor between C 3 and C 4 types.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen counts were performed and converted to grains per cubic meter of air for sites in (from lowest to highest latitude) Darwin (two sites), Brisbane, Sydney, Canberra (two sites) and Hobart over 2, 5, 8, 4 and 3 fiscal years, respectively (Dass 2010; Erbas et al 2007b; Green et al 2004; Katelaris and Burke 2003; Newnham et al 1995; Newnham 1999; Stevenson et al 2007, Tng et al 2010). Airborne pollen were counted within the expected grass pollen season of 92 days for Melbourne (October–December) over 13 of the 17 seasons, the others being full years, and between 88 and 134 days for the NZ sites (October–April) over one season.…”
Section: Methodsmentioning
confidence: 99%
“…Pollen loads were validated against those from the secondary sampler. For the first 12 months of the study, these showed similar temporal distribution and loads of each taxa with the following exceptions: the primary sampler has a more urban location, and has the highest values of Arecaceae (palms) and Casuarina pollen, reflecting the proximity of the sample location to suburban gardens (that commonly feature palms) and the coast (where native Casuarina sp predominates); while the secondary site is in closer proximity to the regional savanna landscape and had slightly higher counts for Poaceae, Cyperaceae, and the native conifer Callitris (Stevenson et al, 2007). Some large Callitris plantations were established on the outskirts of Darwin in the 1960s.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Seven taxonomic groups account for 90% of the pollen load. In order of frequency, these are: Myrtaceae (Eucalyptus and Melaleuca trees); Arecaceae (palms); Poaceae (grasses); Callitris (cypress pine); Cyperaceae (sedges); Casuarina (sheoak); and Acacia (wattles), with the remaining 10% composed of approximately 30 different pollen types seen only occasionally and in low numbers (Stevenson et al, 2007). The one major source of outdoor air pollution is vegetation fire smoke during the dry season (Gras et al, 2001).…”
Section: Settingmentioning
confidence: 99%
“…In recent years, several papers have highlighted differences or similarities between pollen counts in the atmospheres of several specific locations in regions with different climates, and relationships between meteorological conditions and atmospheric pollen concentrations (Galán et al 1995;Green et al 2004;Stevenson et al 2007).…”
Section: Introductionmentioning
confidence: 99%